Information-Motivation-Behavioral Skills model of consistent condom use among transgender women in Shenyang, China - Huwen Wang; Ruijie Chang; Qiuming Shen; Lhakpa Tsamlag; Shuxian Zhang; Yue Shi; Tiecheng Ma; Zixin Wang; Rui She; Joseph T. F. Lau; Ying Wang; Yong Cai (BMC, 2020)
Abstract Background The Information-Motivation-Behavioral Skills (IMB) model has received consistent empirical support in the context of HIV prevention among various key populations, but not yet among transgender women (TGW). None effective interventions has been carried out among TGW so far to control their high prevalence of unprotected anal intercourse. The intent of the current study is to examine the application of the IMB model to clarifying the association between condom use correlates and condom use frequency among TGW in China. Methods Using snowball sampling, we recruited 198 self-identified TGW in Shenyang, China from April 2017 to July 2017. Participants were required to complete a questionnaire assessing their background characteristics and IMB model constructs. Structural equation modeling (SEM) was conducted to demonstrate the utility of the IMB model. Results The consistent condom use (CCU) rate was 47.0%. Results of SEM indicated that HIV-preventive motivation (comprising condom use attitude and subjective norms; β = 0.823, P <  0.001) and behavioral skills (including condom use skills and self-efficacy; β = 0.979, P = 0.004) were related to more frequent condom use, whereas HIV knowledge was unrelated to condom use (β = 0.052, P = 0.540). Conclusions The low CCU rate suggested that TGW in China were at high risk of HIV infection and transmission and a key intervention population. HIV-preventive interventions for this population should focus on enhancing motivation and strengthening behavioral skills to increase condom use frequency and reduce HIV infection.